Exosomes released by EBV-infected nasopharyngeal carcinoma cells convey the viral Latent Membrane Protein 1 and the immunomodulatory protein galectin 9 - Hirashima Mitsuomi (BMC Cancer, 2006)
Abstract Background Nasopharyngeal carcinomas (NPC) are consistently associated with the Epstein-Barr virus (EBV). Their malignant epithelial cells contain the viral genome and express several antigenic viral proteins. However, the mechanisms of immune escape in NPCs are still poorly understood. EBV-transformed B-cells have been reported to release exosomes carrying the EBV-encoded latent membrane protein 1 (LMP1) which has T-cell inhibitory activity. Although this report suggested that NPC cells could also produce exosomes carrying immunosuppressive proteins, this hypothesis has remained so far untested. Methods Malignant epithelial cells derived from NPC xenografts – LMP1-positive (C15) or negative (C17) – were used to prepare conditioned culture medium. Various microparticles and vesicles released in the culture medium were collected and fractionated by differential centrifugation. Exosomes collected in the last centrifugation step were further purified by immunomagnetic capture on beads carrying antibody directed to HLA class II molecules. Purified exosomes were visualized by electron microscopy and analysed by western blotting. The T-cell inhibitory activities of recombinant LMP1 and galectin 9 were assessed on peripheral blood mononuclear cells activated by CD3/CD28 cross-linking. Results HLA-class II-positive exosomes purified from C15 and C17 cell supernatants were containing either LMP1 and galectin 9 (C15) or galectin 9 only (C17). Recombinant LMP1 induced a strong inhibition of T-cell proliferation (IC50 = 0.17 nM). In contrast recombinant galectin 9 had a weaker inhibitory effect (IC50 = 46 nM) with no synergy with LMP1. Conclusion This study provides the proof of concept that NPC cells can release HLA class-II positive exosomes containing galectin 9 and/or LMP1. It confirms that the LMP1 molecule has intrinsic T-cell inhibitory activity. These findings will encourage investigations of tumor exosomes in the blood of NPC patients and assessment of their effects on various types of target cells.